Descriptive Epidemiology and Survival Analysis of Prolactinomas and Cushing’s Disease in Korea - Park, Jin Sun; Yun, Soo Jin; Lee, Jung Kuk; Park, So Young; Chin, Sang Ouk (Endocrinology and metabolism (Seoul), 2021)
Only a few studies have established the epidemiology of prolactinoma and Cushing's disease in Korea. Furthermore, the incidence of these disease are increasing than before associated with the development of technologies. This study was designed to evaluate the epidemiology of prolactinoma and Cushing's disease and their survival analysis according to treatment. The nationwide, population-based study evaluated incidence and prevalence of prolactinoma and Cushing's disease using de-identified claims data in The Korean Health Insurance Review and Assessment Service database between 2013 and 2017. The survival analysis investigated regarding treatment over a period of 6 years. A log-rank test and Cox proportional hazard regression analysis were used. The 6,056 patients with newly diagnosed prolactinoma and 584 patients with Cushing's disease were recorded between 2013 and 2017. The annual incidence of prolactinoma was 23.5 cases per million, and its prevalence was 82.5 cases per million, and 2.3 cases per million/year and 9.8 cases per million for Cushing's disease. The survival benefit was insignificant in prolactinoma according to treatment, but treatment of Cushing's disease ameliorated the survival rate significantly. Overall, the incidence of prolactinoma and Cushing's disease was similar with those found previously, but the prevalence of two diseases were inconsistent when compared with the early studies. The present study also proposed necessity of treatment in Cushing's disease for improving the survival rate.